Flowering, floral visitors and climatic drivers of reproductive phenology of two endangered magnolias from neotropical Andean forests (2021)
Depressed fruit and seed production and scant seedling recruitment appear to be imperiling natural populations of Colombian Magnolia species. From February 2015 to April 2017, we recorded data on flowering, pollen limitation, floral visitors, and the reproductive phenology of Magnolia jardinensis and Magnolia yarumalensis, two threatened and endemic species from Colombian Andean cloud forests. Both species are protogynous with anthesis lasting two consecutive days—with M. jardinensis flowers opening in the evening, while M. yarumalensis flowers open early in the morning. Fruit abortion in both bagged flowers and open pollination experiments suggests that both species exhibit considerable reproductive limitations. There was a lower percentage of pollen germination in M. jardinensis (3–26%) than in M. yarumalensis (60–86%), suggesting more limitations in the former species. Magnolia yarumalensis was a prolific fruit producer compared to M. jardinensis, which produced only one ripe fruit during the study, in spite of its high production of floral buds. Despite sharing the same locality, these species did not share pollinators, thus further increasing their vulnerability to extinction. Floral buds in both species were negatively correlated with minimum temperature and precipitation, while ripe fruits in both species were positively correlated with increases in precipitation and temperature. Our results provide information about how climate change could affect the various phenophases of these species. Knowledge about reproductive phenology and life history traits such as flowering and pollinators is crucial for specific and efficient conservation efforts to protect these endangered species under the current climate change scenarios.